Optimal electricity development by increasing solar resources in diesel-based micro grid of island society in Thailand - Prachuab Peerapong; Bundit Limmeechokchai (Energy Reports, 2017)
Isolated grid diesel-based systems have been a basic electricity system in islands in developing countries. Nevertheless, the increasing diesel price and the higher cost of diesel transport to a long distance to the remote islands make the diesel-based systems unsustainable. This study analyzes the viability to increase solar photovoltaic (PV) resources in the existing diesel-based systems. The hybrid PV/diesel system is not only reducing the cost of electricity generation but also decreasing the harmful emissions from fossil fuels. This study uses net present cost (NPC) to evaluate the optimum PV/diesel system configurations for installation in isolated island in Thailand. The results of analyses show that the optimal case PV/diesel system can decrease COE from 0.429/kWh to 0.374/kWh when compared to the existing diesel-based system and can decrease emissions both carbon dioxide of 796.61 tons/yr and other gases of 21.47 tons/yr. The hybrid PV/diesel system also reduces diesel fuel consumption of 302,510 liters per year as a result from an optimal of 41% PV resource shares in this system.
Keywords: 330; Costs of electricity; Diesel generator; Hybrid energy system; Photovoltaic; Sensitivity analysis